Effects of Hydrogel and Salicylic Acid on the Growth And Yield of Mustard Under Rainfed Condition - Mahto, Rakhi; Singh, Rajesh Kumar; Ankita, -; Srivastava , Kartikeya (Bangladesh Journal of Botany, 2023)
A field experiment was conducted during winter (rabi) season of 2017-18 at Varanasi to evaluate the effects of hydrogel as Super Absorbent Polymer (SAP) and salicylic acid (SA) as stress-ameliorating agent, in growth and productivity of Indian mustard (Brassica juncea L.) at rainfed condition. The experiment comprised nine treatments such as Control (T1), Hydrogel (H) @ 2.5 kg/ha (T2), H @ 5 kg/ha (T3), SA 100 ppm (T4), Salicylic acid (SA) 200 ppm (T5), H @ 2.5 kg/ha+ SA 100 ppm (T6), H @ 2.5 kg/ha+ SA 200 ppm (T7), H @ 5 kg/ha+ SA 100 ppm (T8), and H @ 5 kg/ha+ SA 200 ppm (T9). Among the different treatments, soil application of H @ 5 kg/ha and foliar spray of SA@ 200 ppm registered the highest value (mean of two year) of plant height (177.66 cm), primary (7.37) and secondary branches (7.74), siliqua/plant (306.84) as well as maximum seed yield (18.02 q/ha) and straw yield (2344.09 kg/ha). Exogeneous spray of SA alone with higher dose performed better in all parameters than individual application of hydrogel, however, their combination also gave superior result in minimizing moisture stress in plant. Bangladesh J. Bot. 52(1): 27-35, 2023 (March)